2023
DOI: 10.1101/2023.03.28.23287864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery of inhibitory control prefrontal cortex function in inpatients with heroin use disorder: a 15-week longitudinal fMRI study

Abstract: Importance: Heroin addiction and related mortality impose a devastating toll on society, with little known about the neurobiology of this disease or its treatment. Poor inhibitory control is a common manifestation of prefrontal cortex (PFC) impairments in addiction, and its potential recovery following treatment is largely unknown in heroin (or any drug) addiction. Objective: To study inhibitory control brain activity in iHUD and HC, before and after 15 weeks of inpatient treatment in the former. Design: A lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Overall, the addictive process is accompanied by prefrontal cortex dysfunction [50]. While we have not studied a possible reversal of demyelination, studies in heroin users have indicated that abnormal cognitive control can be reversed [51,52], opening up a window of opportunity for the generation of new therapeutic treatments.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the addictive process is accompanied by prefrontal cortex dysfunction [50]. While we have not studied a possible reversal of demyelination, studies in heroin users have indicated that abnormal cognitive control can be reversed [51,52], opening up a window of opportunity for the generation of new therapeutic treatments.…”
Section: Discussionmentioning
confidence: 95%
“…T1-weighted anatomical scans were acquired using a 3D MPRAGE sequence (TR/TE/TI=2400/2.07/1000 ms) with 0.8 mm isotropic resolution, 256 × 256 × 179 mm 3 FOV, 8°flip angle with binomial (1, −1) fat saturation, 240 Hz/pixel bandwidth, 7.6 ms echo spacing, and an in-plane acceleration (GRAPPA) factor of 2. The scan session included other procedures unrelated to the movie reported elsewhere 11,23,[54][55][56][57] . Immediately before and after the movie, subjects were asked to rate their desire for heroin on a scale of 0-9.…”
Section: Mri Acquisition and Moviementioning
confidence: 99%
“…Moreover, while early evidence suggests the potential for structural and functional neural recovery with treatment across SUDs, there are still very few longitudinal studies assessing the effects of treatment-based abstinence in iHUD (see Parvaz et al for a recent review) 10 . Specifically, although we recently reported evidence of recovery of inhibitory control prefrontal cortical (PFC) functions in iHUD 11 , there are no longitudinal studies tracking cue reactivity in iHUD, and none that use engaging naturalistic stimuli for the study of this group's shared brain responses and their potential change with treatment.…”
Section: Introductionmentioning
confidence: 99%